A synopsis of Bambusoideae (Poaceae) in Lombok, Indonesia - I Putu Gede P. Damayanto; Himmah Rustiami; Miftahudin; Tatik Chikmawati (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Damayanto IPGP, Rustiami H, Miftahudin, Chikmawati T. 2020. A Synopsis of Bambusoideae (Poaceae) in Lombok, Indonesia. Biodiversitas 21: 4489-4500. There is little documentation of bamboo on Lombok. Non-native Indonesian bamboos have been reported occurring in Lombok. As such, suspicious bamboo specimens and information in those reports need to be examined and possibly re-determined. This study aimed to provide updated taxonomical information of bamboo species in Lombok and to investigate the accuracy of previous studies regarding the existence of several non-native Indonesian bamboo species on the island (i.e. they do not have original distribution in Indonesia). Data from fieldwork were combined with specimens in Herbarium Bogoriense to create a synopsis of bamboo in Lombok and to develop an identification key to the species. Eleven species of bamboos in Lombok were reported from this study, namely Bambusa glaucophylla, B. maculata, B. multiplex, B. spinosa, B. vulgaris, Dendrocalamus asper, Gigantochloa apus, G. atter, Schizostachyum brachycladum, S. lima, and Thyrsostachys siamensis. Several doubtful species (B. albustiata, B. ventricosa, Guadua angustifolia, S. jaculans, Pseudosasa japonica) were presented to clarify the existence of a non-native Indonesian bamboo in Lombok. Moreover, there is not enough evidence to state Dinochloa sp. occurred in Lombok. The results of this study can be used by stakeholders for bamboo identification and as the baseline taxonomic account for future studies and conservation of bamboo species in Lombok.